Continuous flow photocatalytic reactor using TiO2‐coated foams, modeling and experimental operating mode. Issue 4 (29th November 2022) - Goetz, Vincent; Dezani, Chloé; Ribeiro, Enrique; Caliot, Cyril; Plantard, Gael
Abstract: This article aims to build a modeling and simulating tool of the operation of a continuous flow heterogeneous photocatalysis reactor. Continuous flow is well‐known in reactor engineering for allowing advanced control of reactor and scaling‐up with great confidence, but little research has addressed it's potential for this kind of application. In developing this model, particular attention was paid to the coupling which occurs at local scale between the radiative transfer and the reaction kinetics of advanced oxidation of a target organic micro‐pollutant. The solution of the radiative transfer equation by Monte Carlo method was applied to a photocatalyst supported on a macroporous ceramic foam forming an efficient 3D support. After identification of the kinetic law of degradation, the dynamic simulation model was validated through comparison with a series of experiments performed for different but constant irradiations and for variable irradiations approaching, in term of intensity and dynamics, natural solar radiation.